Islamic finance - Hassan, M.khabir and Lewis, Mervyan K.; Series Editor Mark Blaug (Cheltenham, UK Elgar, 2007)
Islamic Finance' provides source material for researchers and students of Islamic finance, and will be an essential purchase for libraries that have specialist works in this field, as well as those that lack such collections, but which need to provide support material for lone researchers or small student groups.
INclude index
Keywords: Banks and banking--Religious aspects--Islam -- Finance--Religious aspects--Islam -- Sammelwerk -- Collection of articles of several authors